OLIY TA’LIMDA TALABALARGA XORIJIY TILLARNI O‘QITISHDA INNOVATSION TA’LIM TEXNOLOGIYALARIDAN FOYDALANISHDA PEDAGOGIK KOMPONENTLIK - Kiyasova, A.; Koyshibaeva, G. (SCIENCE and SOCIETY, 2022)
The article deals with innovative educational technologies, modern information technologies in the educational process, ways of effective use of interactive methods. Recommendations are given on the effective use of effective methods of working with students in teaching a foreign language in higher educational institutions.
Keywords: interactive methods; teacher; innovation; Step by Step; Venn Diagram; knowledge; skill; qualification; efficiency; evaluation